Development of a PBL-Based e-module to improve the critical thinking skills of deaf and speech-impaired students - Faida Musaad; Hidayani Hidayani; Wa Ode Rusnia; Salama Bafadal; Sulkipli Sulkipli (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
In mathematics education, the integration of innovative approaches is essential to support deaf students' mastery of mathematical concepts. Students with special needs exhibit learning characteristics distinct from their typically developing peers, requiring educators to possess specialized pedagogical skills that facilitate the development of critical thinking.. Observations conducted at a Special School (SLB) in Sorong City revealed that mathematics instruction remained conventional and lacked teaching materials capable of effectively stimulating critical thinking among students with special needs. This study, therefore, aims to develop an interactive e-module grounded in Problem Based Learning (PBL) that is valid, practical, and effective in enhancing critical thinking skills. The research employed the ADDIE model and involved 10 SDLB students as participants. The resulting e-module received a material expert validity score of 4.46 and an average media expert validity of 3.36. Furthermore, the average student score of 54.09 indicated that this e-module was effective in fostering students' critical thinking skills. In terms of learning outcomes, the average pretest score of 30,100 increased to 84,500 post-intervention, with an average N-gain of 54.00, classified within the “highly effective” category. These findings suggest that the development of PBL-based-e-modules significantly enhnaces the critical thinking skills of deaf and speech-impaired studentsspeech-impaired.